Validación de la versión reducida de la escala de depresión geriátrica en el consultorio externo de geriatría del Hospital Nacional Cayetano Heredia - De la torre Maslucan, Jeanie (2024)
Objective: to validate the short form (4 questions) of the geriatric depression scale in elderly adult patients. Material and method: the study was performed from September 2002 to June 2003. We included 400 patients aged 60 and older in the geriatrics outpatient clinic of the Hospital Nacional Cayetano Heredia. The participants were not receiving antidepressant therapy and had no evidence of cognitive deterioration. The tests applied were the DSM-IV (gold standard), the 15-item geriatric depression scale (GDS-15) and the 4-item geriatric depression scale (GDS-4).  Results: the average age was 70,85 years (range 60-98 years); 66,25% were women. 17,3% had depression according to DSM - IV, 11,8% according to GDS - 15 and 34,3% according to GDS-4. The sensitivity of the GDS-15 was 49%; specificity 96%, negative predictive value 90% and positive predictive value 72%. The sensitivity of the GDS - 4 was 93%, specificity 78%, negative predictive value 98% and positive predictive value 47%. The Kappa value for the GDS-15 relative to the DSM-IV was 0,52 and for the GDS-4 was 0,50. Conclusion: the GDS-4 had high sensitivity and negative predictive value, so it could be a useful screening tool for depression in elderly adults, and would save time when attending such patients.